Inconsistency without irrationality - Weber, Konstantin (Grazer Philosophische Studien, 2019)
Every theory of rationality worth taking seriously implies that it is in some way irrational to accept contradictions. In this essay, the author examines how exactly this basic idea should be spelled out. He argues for two claims. First, it is not practically irrational to accept a contradiction in the sense of causing oneself to have contradictory beliefs. Second, it is moreover not theoretically irrational to accept a contradiction in the sense of having contradictory beliefs, if the contradictoriness of the relevant beliefs is inaccessible to the person. The contradictoriness of a set of beliefs is accessible to a person only if this person possesses the general cognitive capacities to realise that the beliefs are contradictory.
CRIS-Team Scopus Importer:2019-12-17
Keywords: accessibility; belief; consistency; contradiction; rationality